Domestication‐related variation in social preferences in chickens is affected by genotype on a growth QTL. (25th January 2013) - Wirén, A.; Wright, D.; Jensen, P.
<x xml:space="preserve">Abstract</x> A growth‐related QTL on chicken chromosome 1 has previously been shown to influence domestication behaviour in chickens. In this study, we used Red Junglefowl (RJF) and White Leghorn (WL) as well as the intercross between them to investigate whether stress affects the way birds allocate their time between familiar and unfamiliar conspecifics in a social preference test ('social support seeking'), and how this is related to genotype at specific loci within the growth QTL. Red Junglefowl males spent more time with unfamiliar chickens before the stressful event compared to the other birds, whereas all birds except WL males tended to spend less time with unfamiliar ones after stress. A significant QTL locus was found to influence both social preference under undisturbed circumstances and social support seeking. The WL allele at this QTL was associated not only with a preference for unfamiliar individuals but also with a shift towards familiar ones in response to stress (social support seeking). A second, suggestive QTL also affected social support seeking, but in the opposite direction; the WL allele was associated with increased time spent with unfamiliar individuals. The region contains several possible candidate genes, and gene expression analysis of a number of them showed differential expression between RJF and WL of AVPR2 (receptor for vasotocin), and possibly AVPR1a (another vasotocin receptor) and NRCAM (involved in neural development) in the lower frontal lobes of the brains of RJF and WL animals. These three genes continue to be interesting candidates for the observed behavioural effects.